Dermatologic Manifestations In Chronic Kidney Disease Patients On Hemodialysis - Shrestha, P; Mathur, M (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Introduction: Dermatologic changes are frequently seen in chronic kidney disease (CKD) patients. Early identification of these manifestations helps timely institution of treatment and prevention of progression of CKD. Objectives: The aim of this study was to evaluate the frequency and pattern of dermatologic problems among CKD patients who are on maintenance hemodialysis in our population. Material and Methods: A hospital based cross sectional comparative study was conducted. Fifty patients with CKD on hemodialysis were compared with the same number of non CKD patients. All the patients were clinically examined. Complementary diagnostic measures such as skin biopsy, gram stain, potassium hydroxide mounting and culture sensitivity of the lesions were carried out when necessary. Results: At least one dermatologic manifestation was present in 86% of the patients and changes were seen commonly in CKD patients who had GFR <15ml/min (83.8%). Cutaneous manifestations were significantly associated with CKD patients than control (p<0.001) but not with the duration of CKD and duration of hemodialysis. Thirty seven patients (74%) were having cutaneous lesions, commonest being xerosis (52%) followed by pruritus (40%) and hyperpigmentation (32%). Nail, mucous membrane and hair changes were present in 56%, 22% and 12% respectively, commonest being white nail (30%), furred tongue (18%), telogen effluvium (10%) respectively. Conclusion: In our study, dermatologic manifestations were common in CKD patients with GFR <15ml/min. Cutaneous and nail changes were seen in 74% and 56% of the CKD patients undergoing hemodialysis, commonest changes being xerosis and white nail respectively. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10594 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014 pp.34-40